Opisthonema libertate ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Opisthonema libertate (Günther, 1867). Deepbody Thread Herring or Pacific Thread Herring. To about 30 cm (11.8 in) TL (Amezcua Linares 1996). Port Hueneme, southern California (Lea and Rosenblatt 2000) to Chile (Pequeño 1l989), including Gulf of California (Whitehead and Rodríguez-Sánchez in Fischer et al. 1995) and Islas Galápagos (Grove and Lavenberg 1997). Marine and brackish waters (Fricke et al. 2020); depth: surface (nightlight; Personal communication: Scripps Institution of Oceanography Fish Collection, La Jolla, California), intertidal to at least 70 m (3–230 ft) (min.: Personal communication: Scripps Institution of Oceanography Fish Collection, La Jolla, California; max.: Velasco and Thiel 2002). ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 44, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...